Measurement of Arterio-Venous Ratio for Detection of Hypertensive Retinopathy through Digital Color Fundus Images - Rani, Anju; Mittal, Dr.Deepti (British Journal of Healthcare and Medical Research, 2015)
Hypertensive retinopathy is a retinal vascular damage caused by high blood pressure which results in loss of vision. In the present work, effort has been devoted to enhance and segment the retinal vasculature which is required to calculate its anatomical characteristics such as width, length for the quantitative measurement of arterio-venous ratio (AVR). Enhancement of the retinal fundus images is done using top-hat transform and segmentation of the vessels using iterative thresholding. The performance of the proposed method is tested on 50 digital fundus images of publicly available MESSIDOR dataset. The hypertensive retinopathy can be measured quantitatively by detecting the decrement in the ratio of width of retinal artery-vein to that of the normal images. The arterio-venous ratio obtained by applying the proposed methodology was found to be 0.62-0.735 in normal cases and 0.203-0.495 in case of patients suffering from hypertensive retinopathy on MESSIDOR dataset which was not performed earlier. This measurement of arterio-venous ratio will be further helpful to identify the stages of hypertensive retinopathy.